Hubungan Antara Penggunaan Gadget dengan Perkembangan Bahasa Anak Usia Dini - Arum Kusuma Dewi; Yuyun Yulianingsih; Tuti Hayati (Jurnal Pendidikan Raudhatul Athfal, 2019)
The results of the preliminary study in RA Al-Wafi's group showed that, there were several problems related to the use of gadgets with language development including many parents who relied on gadgets to make their children become "calm" or not fussy by tipping video shows or opening youtube. The purpose of this study is to find out the use of gadgets; language development and the relationship between the use of gadgets and the development of early childhood language. The method used is quantitative correlation. Data collection techniques in this study were through interviews / conversations and observations. The results of calculations on variable X obtained an average value of 1.76. This value is in the interval 1.1 - 2.0 with sufficient categories. Whereas, the Y variable obtained an average value of 2.66. This value is in the interval 2.1 - 3.0 in the good category. The relationship between the use of gadgets and the development of early childhood language is obtained by the correlation coefficient of 0.08. This correlation coefficient number is included in the very weak category because it is in the interval 0,000 - 0,199. The results of the significance test obtained the price of tcount = 0.54 smaller than the price of t table = 2.012. This means that Ho is accepted, in other words there is no significant positive relationship between the use of gadgets and the development of early childhood language. The amount of contribution / influence of the use of gadgets to the development of the language of early childhood is only 0.64%. This shows that 99.36% of language development in early childhood is influenced by other factors.